2016
DOI: 10.1136/heartjnl-2015-308657
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic implication of relative regional strain ratio in cardiac amyloidosis

Abstract: High RRSR is adversely prognostic in patients with cardiac amyloid. This novel tool is both diagnostic and prognostic and may have implications in management and suitability for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(62 citation statements)
references
References 17 publications
1
55
0
6
Order By: Relevance
“…While LVEF may be normal until the advanced stage of disease, reduction in peak systolic wall motion velocities, especially in the longitudinal axis, are present even in early disease 72 . In general, CA alters strain parameters to a much greater degree than other causes of LV hypertrophy and is characterized by a base-to-apex strain gradient (Figure 3, upper right panel) 70, 71, 73 . This is readily appreciated in parametric polar maps that show relative apical sparing of longitudinal strain, representing an important diagnostic clue differentiating CA from other cardiomyopathies 70 .…”
Section: Diagnosing Cardiac Amyloidosismentioning
confidence: 99%
“…While LVEF may be normal until the advanced stage of disease, reduction in peak systolic wall motion velocities, especially in the longitudinal axis, are present even in early disease 72 . In general, CA alters strain parameters to a much greater degree than other causes of LV hypertrophy and is characterized by a base-to-apex strain gradient (Figure 3, upper right panel) 70, 71, 73 . This is readily appreciated in parametric polar maps that show relative apical sparing of longitudinal strain, representing an important diagnostic clue differentiating CA from other cardiomyopathies 70 .…”
Section: Diagnosing Cardiac Amyloidosismentioning
confidence: 99%
“…Recently, relative apical sparing (RAS) of longitudinal strain (LS) by speckle tracking was described as a specific echocardiographic sign of cardiac amyloidosis useful in the differential diagnosis of unclear LV hypertrophy . Furthermore, is has been also shown that RAS LS may serve as an independent prognostic factor in patients with amyloid heart disease . However, the evaluation of RAS LS using standard approach, which is based on the assessment of regional LS of all LV walls, may not be feasible in numerous patients due to suboptimal visualization of anterior as well as anteroseptal wall in apical two‐chamber and long‐axis view, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…early in the course of CA), or amyloid subtype [20, 28]. Apical sparing can be quantified as the relative regional strain ratio (RRSR), calculated as the average apical LS / (average basal + mid LS) [27, 29]. In a cohort of 55 patients with confirmed CA, a RRSR >1 was 93% sensitive and 82% specific for CA compared to HCM or AS [27].…”
Section: Attr-ca Diagnostic and Management Goals In Elderly Adults: Rmentioning
confidence: 99%
“…Strain assessment of 172 patients with CA (56 ATTRwt, 36 ATTRm, 80 AL, mean age 66) demonstrated that impaired LV basal LS was independently associated with all-cause mortality [20]. Of 97 patients with CA (38 ATTR 59 AL, mean age 64) a higher RRSR (indicating more basal and mid ventricular strain impairment relative to the apex) predicted MACE [29]. …”
Section: Prognosticationmentioning
confidence: 99%